(untitled) (Journal of the College of Basic Education, 2022)
The land use attention had been Increased after it became clear that many of the economic and social problems and Urban linked to land directly and indirectly, as is the case in environmental degradation, and became surveying and planning of land use is the scientific method used to overcome these problems and to find appropriate solutions. The population growth and increasing urbanization of the features of the feature of city of Baghdad led to many problems come including the forefront of the housing problem and the inability of the city to provide housing for the growing population, with increasing congestion in the city center began the process of urbanization, the direction of the parties and the consequent This research discusses the Find the phenomenon of urbanization and the consequently reduced expansion of the area of agricultural land at a time when much need to increase agricultural production, the research has reached a set of findings and recommendations.